A strategic management plan for Allah Valley Landscape Development Alliance - Egar, Dunstan D. (School of Management, University of the Philippines Mindanao, 2011)
Allah Valley Landscape Development Alliance is one of the biggest Local Government Units (LGUs) alliances in the Philippines. It was formed in response to a disaster in 2003. It serves as a coordinating, policy-making, and integrated planning body for the LGUs in terms of environment economic, social, and cultural programs. The alliance is an umbrella organization overseeing the implementation of agreed activities during core group and technical group meetings. Its key accomplishment is on environmental advocacy in selected communities. From a total of 205barangays, 45% remain to be prone to flooding and indeed they are also prone to disasters that come with it. The study of the previous executive director, A.M. Bansuan in 2011, revealed that the alliance does not have management structure, finance, human resources and marketing functions. Several members of its policy making body, the Board of Directors (BOD), just send representatives during BOD meetings. Such organizational structure problem is accompanied by the problem on its dependence on LGU contributions, continued forest denudation and slow growth in the local agricultural economy. The emerging considerations this study found were the following: 1. AVLDA should be given more powers and authority over the management of local resources; 2. AVLDA should undergo reorganization to institutionalize the needed programs and the functions of the staff; and 3. The major population is in the industry of agriculture, which should be given assistance followed by tourism. With the three considered propositions and results of the SWOC analysis, the five recommended programs are (1) ?KT?: Knowledge Advancement & Technology Development, (2) PMO and Alliance Strengthening, (3) Resource Mobilization and Fund Generation, (4) ?Kapit Bisig sa Pagpapaunlad ng AVL? (which means, Together for the Progress of AVL), and (5) Policy Advocacy and Enforcement Watch. The granting of authority in the management of resources such as formulating regulations approved by the two Sangguniang Panlalawigan is vital to other programs identified in this plan. The strategy entitled: ?Restructuring AVLDA: Pursuing Authoritative Accountability Over AVL? shall precede this strategic plan and shall be implemented simultaneous with other programs. The methodologies used in this study are conducting key informant interviews, reviewing of secondary data, and use of SWOT and SWOC matrices. The conceptual framework was devised from the input-output analysis by Leontief and comprehensive strategic model of David.